Exam Time Table Scheduling using Graph Coloring Approach - Bania, Rubul Kumar; Duarah, Pinkey (International Journal of Computer Sciences and Engineering, 2025)
One of the most common academic scheduling problems which can be perceived in any educational system is the exam time table generation. The presence of vast numbers of students and offered courses makes it difficult to schedule exams in a limited epoch of time. An appropriate schedule can be designed by utilizing different resources like subjects, teachers, students and classrooms in a way to evade conflicts by fulfilling special types of constraints. Graph coloring is one decent approach which can deal with timetable scheduling problem and can satisfy changing requirements. In this work, we have framed a systemic model by applying graph vertex coloring approach for generating exam timetabling with the help of a course matrix generated from given data of an educational institute. From the problem domain, different types of constraints viz., hard and soft are figured out and while solving emphasis is focused on the degree of constraint satisfaction. Workflow of the system is described by using a case study and the output which it has generated is efficient and satisfactory.